Productive and market potential of bacuri fruit (Platonia insignis Mart.) in Pará, Brazil (Research, Society and Development, 2020)
In order to understand the production and marketing patterns of bacuri (Platonia insignis Mart.) fruit, in the state of Pará, this research aims to present an exploratory analysis of the bacuri's production and market situation. The research used agricultural production data from the 2017 Census of Agriculture of the Brazilian Institute of Geography and Statistics (IBGE) and data from the Central de Abastecimento do Pará (CEASA/PA, 2020). Quantitative and qualitative analyzes were carried out in relation to the data obtained on the bacuri's production and market situation. The results show that there are 1,329 agricultural establishments related to the production of bacuri in Pará. The State corresponds to 49.2% in relation to the total quantity in Brazil, since the country has 2,700 agricultural establishments that carry out the production of bacuri. At the national level, fruit production is concentrated only in two regions: North, where the production was 1,579 tons produced in 2017, contributing 86.4%; and the Northeast, where 248 tonnes were obtained, with a 13.5% share. Altogether the State of Pará produced 1,482 tons and sold 865 tons, representing 58.3% of the quantity produced. It is noted that a little more than half of the total production was sold. Therefore, the bacuri fruit and pulp market is very promising for the State of Pará. However, its production is mostly extractive or managed, which prevents a structured production to meet the product demand.